Experimental study on targeted inhibition of coal spontaneous combustion based on metal catalysis - Yansheng Wang; Ye Liu; Ling Qiao; Bing Lu; Cunbao Deng; Xuefeng Wang (Case Studies in Thermal Engineering)
To achieve targeted inhibition of the catalytic effects of metal elements in coal on the coal spontaneous combustion, this study based on the chelating constants and properties of chelators, hydroxyethylidene diphosphonic acid (HEDP) and ethylenediamine tetramethylenephosphonic acid (EDTMPA) were selected to carry out targeted inhibition treatment on coal samples with high Fe content and high Ca content, respectively. Thermogravimetric and temperature programmed experiments showed that after adding targeted metal chelator, the weight loss and oxygen uptake of coal samples decreased, the characteristic temperatures increased by 10.00–20.00 °C, and the CO release decreased by 15.6 %–98.8 %. In-situ infrared spectroscopy and electron spin resonance experiments showed that the targeted metal chelator combined with metal ions through coordination to form stable compounds, thereby reducing the free radical concentration in coal by 9.38 %–26.92 %. HEDP effectively inhibited Fe3+ catalysis on -OH, and the inhibition rate reached 35.36 %–80.55 % at 110 °C. Compared with EDTMPA, the inhibition rate increased by 18.13 %–33.58 %. EDTMPA was more effectively inhibited Ca2+ catalysis on -CH3 and -C=O. Before about 150 °C, the inhibition rate of -C=O increased by 1.73 %–7.68 % compared with HEDP. This indicates that the targeted metal chelator can more effectively inhibit the low temperature oxidation of coal.